(untitled) (Polifonia, 1997)
ABSTRACT: This article focuses on the poetic works of Manoelde Barros, a mato-grossense poet, and it attempts to maintain the critical dialogue in relation to his poems by emphasizing the composition of the text which determines a model for the renewal of the poetic language initiated in Brazil from the modernist movement.